The Role of Information Systems in Facilitating Collaborative Learning in Higher Education - Hayati, Amelia; Nitin, Mahon; Yunita, Hilda Dwi; Fahurian, Fatimah; Winarko , Triyugo (Journal of Social Science Utilizing Technology, 2024)
Background. The rapid evolution of digital technologies has transformed educational practices, with information systems playing a critical role in enhancing collaborative learning in higher education. Collaborative learning, which emphasizes peer-to-peer interaction and shared knowledge construction, fosters critical thinking, problem-solving, and teamwork skills essential for the 21st-century workforce. Despite its potential, the implementation of effective collaborative learning strategies often faces challenges such as insufficient technological support and lack of engagement. Purpose. This study investigates the role of information systems in facilitating collaborative learning, focusing on their impact on student engagement, knowledge sharing, and learning outcomes. Method. A mixed-method approach was employed, combining quantitative surveys and qualitative interviews with 200 undergraduate students and 20 faculty members across three higher education institutions. Data were collected on the use of information systems such as learning management platforms, virtual collaboration tools, and online forums. Key performance indicators included student engagement, participation rates, and academic performance. Results. The findings revealed that information systems significantly enhance collaborative learning by providing a centralized platform for communication, resource sharing, and real-time interaction. Students reported a 30% increase in engagement and a 25% improvement in teamwork efficiency when using digital collaboration tools. Faculty members highlighted the ease of monitoring and supporting group activities through analytics and reporting features. Challenges such as digital literacy gaps and technical issues were also identified. Conclusion. The study concludes that information systems are pivotal in enabling effective collaborative learning by fostering connectivity, engagement, and accountability among students. Addressing challenges related to accessibility and technical support will maximize their potential in higher education.